Efeito do armazenamento na qualidade dos grãos e do óleo de crambe, para produção de biodiesel - Bezerra, Pedro Henrique Silva [UNESP] (2014)
The crambe, due to its richness in vegetable oil is a great option for the production of biodiesel. Storage is essential for the physiological quality of the grain practice. Packaging used should help slow the process of deterioration, maintaining grain quality. Different combinations of management practices and environmental conditions affect the ability of grain storage silo bag and sacks, providing greater preservation of raw material for the extraction of oil. Thus, this study aims to evaluate the quality of grain and crambe oil under different storage conditions, aiming at the production of biodiesel. The experimental design was completely randomized, triple factorial, with two types of packaging, three environmental conditions and three storage periods, with three replications. Analysis of grain quality were water content, fat acidity, electrical conductivity, color and oil yield. The analysis of oil quality were: iodine value, viscosity, density, acid value and water content. The results were subjected to analysis of variance and means were compared by the t test at 5% probability. The results show that the hermetic packaging resisted the influences of storage and kept the quality of grain and oil, the time 12 months had unsafe levels of quality and climatic chamber environment showed evidence of deterioration in all evaluative questions, packaging and bag and conventional hermetic sacks.